2012
DOI: 10.1371/journal.pone.0050618
|View full text |Cite
|
Sign up to set email alerts
|

[18F]FLT PET for Non-Invasive Assessment of Tumor Sensitivity to Chemotherapy: Studies with Experimental Chemotherapy TP202377 in Human Cancer Xenografts in Mice

Abstract: Aim3′-deoxy-3′-[18F]fluorothymidine ([18F]FLT) is a tracer used to assess cell proliferation in vivo. The aim of the study was to use [18F]FLT positron emission tomography (PET) to study non-invasively early anti-proliferative effects of the experimental chemotherapeutic agent TP202377 in both sensitive and resistant tumors.MethodsXenografts in mice from 3 human cancer cell lines were used: the TP202377 sensitive A2780 ovary cancer cell line (n = 8–16 tumors/group), the induced resistant A2780/Top216 cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Histologic assessments of proliferation markers validated the strong correlation between [ 18 F]FLT uptake and Ki-67 expression after 14 days of treatment, in line with previous reports (47). Expression of TMEM97 also paralleled the uptake of [ 18 F]ISO-1, which confirmed the PET results by indicating that the decrease in tracer uptake was due to a real change in expression of proliferation marker, s 2 -receptor, and not a consequence of decreased delivery of radiotracer.…”
Section: Discussionsupporting
confidence: 89%
“…Histologic assessments of proliferation markers validated the strong correlation between [ 18 F]FLT uptake and Ki-67 expression after 14 days of treatment, in line with previous reports (47). Expression of TMEM97 also paralleled the uptake of [ 18 F]ISO-1, which confirmed the PET results by indicating that the decrease in tracer uptake was due to a real change in expression of proliferation marker, s 2 -receptor, and not a consequence of decreased delivery of radiotracer.…”
Section: Discussionsupporting
confidence: 89%
“…n = 14 of the 122 reports with reduced [ 18 F]FLT accumulation after therapy, demonstrate that at the end of a treatment cycle, [ 18 F]FLT levels might not be distinguishable from baseline, reflecting recovery of tumor proliferation as shown by respective immunohistochemistry 9,15,26-37. Hence, for successful treatment monitoring, the imaging time point is of crucial importance.…”
Section: Resultsmentioning
confidence: 99%
“…Uptake of FLT is assumed to reflect the amount of proliferating cells since TK1 is mainly expressed during the S-phase of the cell cycle [20], [21]. Several studies have found a correlation between uptake of FLT and tumor cell proliferation measured by Ki67 [22]. In a meta analysis of 27 studies, the FLT/Ki67 correlation was found to be strong and independent of cancer-type [23].…”
Section: Introductionmentioning
confidence: 99%